2012
DOI: 10.1097/jac.0b013e318249e0fd
|View full text |Cite
|
Sign up to set email alerts
|

Patient Engagement—What Works?

Abstract: The recent focus on patient engagement acknowledges that patients have an important role to play in their own health care. This includes reading, understanding and acting on health information (health literacy), working together with clinicians to select appropriate treatments or management options (shared decision making), and providing feedback on health care processes and outcomes (quality improvement). Various interventions designed to help patients play an effective role have been evaluated in trials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
283
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 380 publications
(306 citation statements)
references
References 60 publications
5
283
0
7
Order By: Relevance
“…Practitioners can ask the patients what their expectations are for both the treatment process and treatment outcome and whether those expectations are what they think is likely to happen or what they hope to happen. Talking about expectations can open up opportunities for shared decisionmaking between the practitioner and patient, which may result in better patient satisfaction, adherence and treatment outcomes [27,28]. If expectations are unrealistic, then the influencing factors found in this study might be useful targets for changing expectations.…”
Section: Discussionmentioning
confidence: 98%
“…Practitioners can ask the patients what their expectations are for both the treatment process and treatment outcome and whether those expectations are what they think is likely to happen or what they hope to happen. Talking about expectations can open up opportunities for shared decisionmaking between the practitioner and patient, which may result in better patient satisfaction, adherence and treatment outcomes [27,28]. If expectations are unrealistic, then the influencing factors found in this study might be useful targets for changing expectations.…”
Section: Discussionmentioning
confidence: 98%
“…At one end of the continuum are intervention studies that examine tools for patient involvement in professional decisions and review articles about the same. This kind of research is most often concerned with patients’ views of medical treatment [911]. The research represents a disease-oriented approach to patient involvement [12].…”
Section: Introductionmentioning
confidence: 99%
“…4 A systematic review of engagement strategies found that they improved patients' health and reduced health care use and costs. 5,6 And a recent literature review concluded that patient engagement had a positive impact on health outcomes, medication adherence, and rates of hospital admission. 7 Yet medical staff often fail to recognize the advantages of understanding people's experience of illness-how they reacted to the emergence of symptoms, how they felt about and understood their diagnosis and treatment plan, and how equipped they felt to take responsibility for managing aspects of their own care.…”
mentioning
confidence: 99%